A Set Table : Who Sat On My Chair. - Shalev, Neomi; Art Focus Contemporary Israeli Art, Jerusalem 1994 (Tel Aviv : Painters and Sculpture Association Israel, 1994)
Berkowitz, Arie ; Biber, Yael ; Figorich Goddard, Dorit ; Gadalov, Avshalom ; Geldman, Mordechai ; Griffit, Joshua ; Gur, Ronit ; Hameagel, Honi ; Helbitz, Ruth ; Erena & Anat ; Miller, Dina ; Piltz, Erez ; Shavit Bentwich, Rahel ; Shevi, Orly ; Shirman, Simcha ; Sisselman, Mina
A Set Table : Who Sat On My Chair, Painters and Sculpture Association Israel, Tel Aviv, The Opening: 4th October 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek